Banking in the Dock: A Summary Judgment on the Credit Conditions Faced by Firms During Chile's Latest Recession (Observatorio Económico, 2009)
Criticism of Chilean banks has been abundant this year. To the recurring complaint about abusive fees were added grievances about the contraction in the supply of credit and high interest rates, especially in lending to small and medium-sized enterprises (SMEs). This article reviews the statistical information available on commercial loans in light of the main criticisms. The aim is to enrich a debate in which prejudice sometimes shouts louder than the numbers. Continue reading...
Keywords: Chilean banks; commercial loans; lending; interest rates